Sözleşme özgürlüğünün sınırı olarak emredici hükümlere aykırılık - Örs, Mehmet Nuri (My University, 2004)
Sözleşme özgürlüğünün sınırlarından birini teşkil eden emredici hükümler, özel hukukun yanında kamu hukuku ve bütün hukuk sisteminin önemli temel hukuk kurallarındandır. Kural olarak, herkes sözleşme özgürlüğüne sahiptir. Kişilerin özellikle özel hukuk ilişkilerinde, istediği kişiyle, istediği şekilde, türde, sürede, içerikte ve istedikleri zamanda sona erdirmek üzere sözleşme yapabilmeleri, özel hukuktaki bireysel özgürlüğün sonucudur. BK. m. 19/ 1'de ifade edildiği gibi; kişiler, hukuk düzeninin sınırları içerisinde kalmak kaydıyla sözleşme özgürlüklerine sahiptir. Hukuk düzeninin bu sınırlarından en önemlisi ve belki tek sınırı emredici hükümlerdir. Kanun koyucu, bireyin veya toplumun üstün menfaatlerini gördüğü alanlarda, kişilere, irade serbestisi, dolayısıyla da sözleşme serbestisi tanımayarak, onlara sınırlar getirmiş ve bu sınırlara uyma mecburiyeti sağlayarak; emredici olan bu sınırlamalara aykırı olarak yapılan sözleşmelere hayatiyet vermemiş, onları bazı yaptırımlara tabi tutmuştur. Sözleşme özgürlüğü, olumlu ve olumsuz müdahalelerle sınırlandırılmıştır. Olumlu müdahaleler; sözleşme yapma mecburiyeti, sözleşmenin edimlerinde ki değer sınırlandırmaları, geçerlilikleri kamu organlarının iznine bağlı sözleşmeler ve sözleşmenin yeni durumlara uydurulmasıdır. Olumsuz müdahaleler ise, başta emredici hükümler olmak üzere, kamu düzeni, şahsiyet hakları, ahlak kuralları, sözleşmenin konusunun imkansız olmaması, gabin ve dürüstlük kuralı ile hakkın kötüye kullanılması yasağıdır. Bunlar hepsi sözleşme özgürlüğü sınırlarlar. Fakat bunların hepsi geniş anlamda, emredici hükümlerin kapsamına girmektedir. Zira, BK. m. 19 ve diğer hukuk kurallarıyla, sınır getirmektedirler. Kamu hukuku alanında da, emredici hükümlerin büyük bir ağırlıkları vardır. Zira, kamu yararının mevcut olduğu bu hukuk dalında, hükümlerin tamamına yakını emredicidir. Başta anayasa olmak üzere, ceza, idare, vergi gibi hukuk dallarında, bireyin uymak zorunda oldukları hukuk kuralları öngörülmüştür. Kanunlar ve diğer hukuk kaynakları anayasaya aykırı olamayacaklarına göre, kişiler de, sözleşme düzenlerken, anayasanın hükümlerine uymak zorundadırlar. Aynı şekilde ceza hukukunda, ceza hukuku kurallarının ihlal halinde bireylerin özgürlüklerinin kısıtlanması sonucunu doğuran cezaların uygulanması, bu hukuk dalının da emredici hükümlerin mevcut olduğunun açık göstergeleridir. Bir hükmün emrediciliği, bazen kanun hükmünün ifadesinden, bazen yasaklayıcı veya mecbur edici olması gibi ifadelerle içeriğinden anlaşılabilir. Bazı durumlarda ise; kamu yararı, kişilik haklarının korunması, genel ahlak, zayıfın korunması gibi düşüncelerle kabul edildiklerinden, emredici oldukları tespit edilebilir. Emredici hükümlere aykırılığın çeşitli yaptırımları vardır. Bu yaptırımların başında butlan gelmektedir. Nitekim, emredici hükümlere aykırılığın genel yaptırımını düzenleyen BK. m. 20/ 1 hükmü, butlanı esas almıştır. Emredici hükümler, sözleşmenin kurucu unsurlarını öngördüğü hallerde, bu kurucu unsurlar yoksa, yokluk yaptırımı sözkonusu olur. Yokluk ve butlan, mutlak geçersizlik halleri ve en ağır yaptırımlardır. Fakat, bazı emredici hükümler yokluk ve butlan müeyyidesini gerektirmeyecek derecede hafiftirler. Bu durumda askıda hükümsüzlük halleri olan; eksiklik, iptal edilebilirlik, sözleşmenin feshi uygulanır. Kanunkoyucunun geçerli bir sözleşmenin kurulması ve hükümlerini doğurması için aradığı unsurlar eksikse, eksiklik yaptırımı sözkonusu olur. Tarafların menfaatlerinin esas alındığı bazı hususlarda, eksiklik varsa, iptal edilebilirlik; üçüncü kişilerin veya kamunun menfaatlerin mevcut olduğu hallerde ise fesih sözkonusu olur. The imperative provisions, one of the limits of the freedom of contract, are also the major legal rules of the private law and the public law as well as the whole law system. As a rule, everybody has the freedom to make contracts. It is an outcome of the individual freedom in the private law for persons to make contracts especially in their private law matters with anybody and in any form, time, contents and expiration date they want. As stated in Article 19/ 1 of the Turkish Code of Obligations, persons are free to make contracts provided that they will act within the limitations of the legal system. The most important of these limitations and perhaps the only limitation of the legal system is the imperative provisions. The lawmaker does not bestow upon persons the freedom of initiative and therefore the freedom of contract where it considers there are more significant interests of the individual or the society, and limits them, and imposes upon them the obligation to abide by such limitations, and annuls the contracts executed not in accordance with such imperative limitations, and subjects them to some sanctions. The freedom of contract has been limited with positive and negative interventions. The positive interventions are the obligation to make contracts, limitations of value in the acts of contracts, contracts whose validities are up to permissions by public offices, and adaptation of contracts to new circumstances. The negative interventions are the imperative provisions in the first hand, as well as the public order, personal rights, moral rules, intervention against impossibility of the subject of the contract, fraud and honesty rule, and prohibition of misuse of rights. These all limit the freedom of contract. However, these are all under the scope of the imperative provisions in a broader sense because they impose limitations with Article 19 of the Turkish Code of Obligations as well as the other legal rules. The imperative provisions have a significant effect also in the public law because in this branch of law where the public interest is present almost all provisions are imperative. The legal rules which the individuals are obliged to abide by have been set forth in the constitution as well as in the other branches of law such as criminal law, administrative law and tax law. Since the laws and the other legal sources cannot be contrary to the constitution, persons are obliged to abide by the constitutional provisions while they execute any contract. Likewise, imposing of the punishment of restriction of individuals' freedom in the criminal law upon any violation of the provisions of the criminal law expressly indicates that this branch of law also has imperative provisions. The imperativeness of a provision of a law can sometimes be understood from its expression, and sometimes from its content with expressions like prohibiting or obligating. In some cases, they can be considered imperative as they have been accepted for ideas like the public interest, protection of personal rights, general moral rules, and protection of the weak. Contradiction to imperative provisions has various sanctions. Nullity is the first among these sanctions. Likewise, Article 20/ 1 of the Turkish Code of Obligations, which sets forth the general sanction of contradiction to imperative provisions, is based on nullity. In the event that the imperative provisions provide for the establishing components of the contract where such establishing components are not present, then absolute nullity sanction will apply. Absolute nullity and nullity are the absolute invalidity situations and are the most serious sanctions. However, some of the imperative provisions are very slight and do not require absolute nullity or nullity sanctions. In this case, the pendent invalidity situations, which are absence, revocability, and termination of the contract will apply. In the event that the components which the lawmaker seeks for the establishment and bringing forth of the provisions are incomplete, then an absence sanction will apply. In some cases where the interests of the parties are the basis, if there is any absence, then revocability will apply; and in cases where the interests of third parties and the public are the basis, then termination will apply.
Keywords: Hukuk; Özel Hukuk